Evaluating the Transformations of the Bura Biosphere Reserve in Yemen: A reading of the Environmental, Social, and Economic Context - Al-Okab, Bardees Taher (Journal of Economic, Administrative and Legal Sciences, 2025)
The establishment of protected areas is a crucial step towards improving the environment, protecting wildlife and marine life, mitigating degradation, conserving biodiversity, and promoting ecotourism. They also play a role in protecting ecosystems and supporting climate regulation. The designation of these areas promotes sustainable livelihoods, raises environmental awareness, and enhances communities’ resilience through sustainable resource management. This paper aims to explore the transformations that Bura’a Biosphere Reserve in Yemen has witnessed since its inscription on UNESCO’s tentative list in 2002, through its declaration as a national reserve in 2006, and finally its registration as a Biosphere Reserve on the UNESCO List in 2011. The study focuses on analyzing the environmental, social, and economic context of each phase, exploring the key challenges and opportunities the reserve faced during these stages. The study adopted a qualitative descriptive approach, using analytical chronology and case study methods to document and analyze the reserve’s development. The study concludes that each phase has experienced environmental, social, and economic challenges, shaped by changing political circumstances, economic instability, and the effects of climate change. The trajectory of the Bura’a Biosphere Reserve reflects a complex interplay of these factors. The study revealed that conservation efforts have been significantly hampered by environmental changes, such as climate-induced drought, as well as weak management and the inability to enforce laws.